2020
DOI: 10.1016/j.dib.2020.106142
|View full text |Cite
|
Sign up to set email alerts
|

Impact of female students’ perceptions on behavioral intention to use video conferencing tools in COVID-19: Data of Vietnam

Abstract: This paper presents the dataset of a survey on Vietnamese female students’ behavioral intention to use video conferencing tools (VCTs; e.g. Zoom, Microsoft Teams or Google Hangout) in COVID-19 pandemic. The questionnaire was designed based on the Technology Acceptance Model according to the result of research conducted by [1] and [2] . The survey was conducted on an online platform using the questionnaire of 21 items to collect the information of respondents’ chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 6 publications
2
26
0
7
Order By: Relevance
“…Likewise, Google as an online platform, has been highly evaluated as useful due to the fact that it is easy to use. Similarly, studies by [20,27] are consistent with the results that are found in the current study regarding PU and PEOU since PU and PEOU have positively affected the acceptance of Google Meet and helped in forming a conceptual framework to the students' reaction of fear during the spread of Coronavirus.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Likewise, Google as an online platform, has been highly evaluated as useful due to the fact that it is easy to use. Similarly, studies by [20,27] are consistent with the results that are found in the current study regarding PU and PEOU since PU and PEOU have positively affected the acceptance of Google Meet and helped in forming a conceptual framework to the students' reaction of fear during the spread of Coronavirus.…”
Section: Discussionsupporting
confidence: 89%
“…Concerning the perceived fear factor, studies by [2,11,19,20] tackled the fear factor from different perspectives in the educational sector. According to these studies, fear has different forms, such as fear of stress, fear of loss of the academic year, fear of usefulness, fear of satisfaction, fear of usability, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, to achieve successful learning, students must progressively develop their capacity for self-regulation, defining their own study schedules [ 26 ], which have to be perceived as an obligation to become a habit [ 27 ]. However, the first wave of the COVID-19 pandemic, the consequent lockdown, and the interruption of F2F classes meant that teaching had suddenly to be adapted to online methodologies [ 28 ] for which neither teachers nor students were prepared [ 29 ]. This situation might imply that concepts were not learnt as well in online classes as they had been in F2F classes, with the inevitable conclusion that the teaching quality was worse [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Umacharan, Said, and Estabraq [11] discussed the broadcasting platforms e.g., Google meet, Teems, WebEx, Hangouts, Zoom, FreeConferenceCall to distant locations through video performances and also through indigenously advanced conferencing platforms stand allied to complete with the internet, converting distance education or e-learning as forthcoming cardinal erudition. The survey of Bui et al, [12] presented the behavioural intention of Vietnamese female students (N=254) to use video conferencing tools (VCTs; e.g., Zoom, Microsoft Teams, or Google Hangout) in the COVID-19 pandemic. Similarly, Al-Maroof et al, [13] attempted to explore the effect of Google Meet acceptance among Arab students (N=475) during the pandemic in Oman, UAE, and Jordan.…”
Section: The Literature Reviewmentioning
confidence: 99%